Global 5-Hydroxymethylcytosine Levels Are Profoundly Reduced in Multiple Genitourinary Malignancies - Munari, Enrico (PLoS One, 2016)
Solid tumors are characterized by a plethora of epigenetic changes. In particular, patterns methylation of cytosines at the 5-position (5mC) in the context of CpGs are frequently altered in tumors. Recent evidence suggests that 5mC can get converted to 5-hydroxylmethylcytosine (5hmC) in an enzymatic process involving ten eleven translocation (TET) protein family members, and this process appears to be important in facilitating plasticity of cytosine methylation. Here we evaluated the global levels of 5hmC using a validated immunohistochemical staining method in a large series of clear cell renal cell carcinoma (n = 111), urothelial cell carcinoma (n = 55) and testicular germ cell tumors (n = 84) and matched adjacent benign tissues. Whereas tumor-adjacent benign tissues were mostly characterized by high levels of 5hmC, renal cell carcinoma and urothelial cell carcinoma showed dramatically reduced staining for 5hmC. 5hmC levels were low in both primary tumors and metastases of clear cell renal cell carcinoma and showed no association with disease outcomes. In normal testis, robust 5hmC staining was only observed in stroma and Sertoli cells. Seminoma showed greatly reduced 5hmC immunolabeling, whereas differentiated teratoma, embryonal and yolk sack tumors exhibited high 5hmC levels. The substantial tumor specific loss of 5hmC, particularly in clear cell renal cell carcinoma and urothelial cell carcinoma, suggests that alterations in pathways involved in establishing and maintaining 5hmC levels might be very common in cancer and could potentially be exploited for diagnosis and treatment.